ESSENCE AND PLACE OF COMPARATIVE PEDAGOGY IN THE SYSTEM OF PEDAGOGICAL SCIENCES (ResearchJet Journal of Analysis and Inventions, 2022)
In the article, the development stages and new trends of comparative pedagogy in connection with the processes of integration in education are outlined. The tasks of comparative pedagogy to determine the positive and negative aspects of the development of education in different countries, to study the socio-political and economic conditions that determine the occurrence of these phenomena, to determine how it affects the social development of the region and the whole world, and to forecast the consequences of the impact are analyzed.